Nitrogen-doped carbon dots from Brahmi (Bacopa monnieri): Metal-free probe for efficient detection of metal pollutants and methylene blue dye degradation - Soman Kondetharayil; Kanagaraj Kuppusamy; Senthilkumar Nangan; Rajendran Saravanan; Faraj Turki Kh.; Alrefaei Abdulwahed Fahad; Thirumalaivasan Natesan; Sundaram Thanigaivel; Roy Arpita; Verma Rajan; Thomas Sabu; Gopi Sreeraj; et al. (Green Processing and Synthesis, 2025)
Contaminants like heavy metals in water bodies pose serious risks to human health and ecosystems, often leading to acute and chronic disorders, including cancer and organ damage. Understanding water contamination is vital for sustainable development. A biosensor is a biocompatible, sustainable device that can detect heavy metal ions. To do this, we used a hydrothermal process to produce nitrogen-doped carbon dots (NCDs) from the plant Brahmi (Bacopa monnieri), given that Brahmi is a novel material for the synthesis of carbon dots and a medicinal plant. The nanoparticles’ size and morphology were analyzed using high-resolution transmission electron microscopy, field emission scanning electron microscopy, and dynamic light scattering techniques, while Raman spectroscopy, Fourier transform infrared spectroscopy), and X-ray diffraction spectroscopy were employed for sample characterization. Optical properties were studied using ultraviolet (UV) and fluorescence spectroscopy. The NCDs showed a high quantum yield of 15.7%, and demonstrated significant fluorescence quenching in the presence of Fe³⁺ and Ni²⁺ ions, with detection limits of 1.46 and 3.19 µmol·L−1, respectively. This rapid, accurate method offers a promising solution for detecting heavy metals in water and could be expanded to real water samples and photocatalytic degradation of methylene blue dye under UV light.